A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying

The preparation of titanium oxide-doped silicon-carbon composite materials by sand grinding combined with spray drying solves the problems of complex preparation process, high cost and unstable electrochemical performance in the prior art, and realizes a simple and scalable preparation process and high efficiency electrochemical properties.

CN115498149BActive Publication Date: 2025-02-14FUJIAN NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211074625.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-02-14
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have problems such as complex preparation process, high cost and unstable electrochemical performance in the application of lithium-ion battery negative electrodes, especially in terms of large-scale industrial production and economic benefits.

Method used

The titanium oxide-doped silicon-carbon composite material was prepared by sand milling combined with spray drying. Micron-scale Si particles and commercial graphite were treated by sand milling to form a uniform mixed slurry, and carbon source PVP and titanium oxide precursor were added. Spray drying and calcining annealing treatment to produce silicon-carbon composite anode material with excellent electrochemical properties.

Benefits of technology

It realizes a simple and scalable preparation process, reduces production costs, improves the electrochemical stability and cyclic performance of the materials, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115498149B_ABST
    Figure CN115498149B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium ion battery electrode materials, and relates to a method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying. The method first disperses micron silicon powder in anhydrous ethanol for sand grinding, then continues to add graphite and PVP for sand grinding, and finally adds a certain amount of titanium oxide precursor, and obtains a mixed slurry after uniform stirring; the slurry is spray dried to obtain a silicon carbon composite material precursor powder; and the silicon carbon composite negative electrode material is obtained after high temperature calcination and annealing. Based on the preparation process of button half-cell, coating and testing are carried out to obtain a silicon carbon negative electrode material with a first discharge capacity of 1525.3 mAh / g, and at a current density of 800 mA / g, the capacity is 876 mAh / g, and the retention rate is 88.3%. The present invention provides a synthesis strategy for improving the conductivity and interface compatibility of lithium ion battery materials by using metal oxides and organic carbon sources, and the synthesized silicon carbon composite negative electrode material has a simple and efficient preparation method and significantly improves the electrochemical performance, which is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing titanium oxide-doped silicon-carbon lithium ion battery negative electrode material by combining sand grinding with spray drying, belonging to the technical field of lithium ion battery material preparation. Background Art

[0002] In recent years, the application of negative electrode materials is still dominated by commercial graphite. However, due to the low theoretical specific capacity of graphite negative electrode (370mAh / g), the further development of today's energy is greatly restricted. As a negative electrode material for lithium-ion batteries, silicon has quickly come into everyone's attention due to its high theoretical specific capacity of 4200mAh / g and its abundant reserves in the earth's crust. It is considered to be the next generation of negative electrode materials with the most commercial prospects and has become the focus of research at this stage. However, studies have found that during the charge and discharge cycle, the volume of silicon particles will expand and shrink dramatically (~300%), causing the silicon particles to rupture and the structure to be destroyed, resulting in the formation of an unstable solid electrolyte membrane (SEI), accompanied by the collapse of the conductive network, which reduces the conductivity, causing the capacity of the material to drop sharply, and the electrochemical cycle stability is poor.

[0003] At present, in order to overcome the main problems of silicon, a large number of researchers have alleviated the volume expansion problem by nano-sizing, alloying, and compounding with other active materials, which has greatly improved the conductivity and cycle stability. For example, carbon-based materials have high conductivity and good cycle stability, and compounding with silicon can greatly improve the electrochemical performance of the material; doping with metal oxides can improve the compatibility of silicon interfaces and further improve the cycle stability of silicon composite materials. These have been widely studied by researchers at home and abroad.

[0004] For example, CN109216686B discloses a lithium-ion battery silicon-carbon composite material and a preparation method thereof: the composite material is prepared by mixing nano-silicon, carbon material, metal salt and organic carbon source solution, and then subjected to spray pyrolysis and sintering carbonization. The porous secondary structure of the composite material effectively improves the tap density and adapts to the volume expansion of silicon to reduce mechanical stress.

[0005] CN112310363A of Huawei Technologies Co., Ltd. discloses a silicon-carbon composite material, a preparation method thereof and a lithium-ion battery, and provides a silicon-carbon composite material with a graphite skeleton, amorphous carbon filled in the graphite skeleton structure, and silicon material uniformly distributed in the amorphous carbon as the core, and a uniform carbon layer coated on the surface.

[0006] Yu-Guo Guo et al. reported a spherical Si / C particle with a three-dimensional conductive network as a negative electrode for lithium-ion batteries using a spray drying method, and had an ultra-high loading specific capacity (Xu Q, Sun JK, Li JY, et al. Scalable synthesis of spherical Si / C granules with 3D conducting networks as ultrahighloading anodes in lithium-ion batteries[J]. Energy Storage Materials, 2018, 12: 54-60).

[0007] CN102790204A discloses a method for preparing a silicon-carbon lithium-ion battery negative electrode material. The method comprises the steps of first mixing a polymer solution with silicon powder and graphite to obtain a mixed solution, then freeze-drying to remove the solvent, and finally sintering at a high temperature to obtain the silicon-carbon lithium-ion battery negative electrode material.

[0008] CN110021749A discloses a silicon-carbon negative electrode material and a preparation method thereof: nano silicon, an organic dispersant and graphene oxide are added to a solvent to form a first solvent, which is then spray dried and then annealed and sintered to obtain a silicon-carbon negative electrode material with a simple preparation process.

[0009] CN113258063A discloses a method for preparing graphite negative electrode materials for lithium-ion batteries by spray drying: needle coke powder or petroleum coke powder or graphite powder, asphalt slurry, CMC glue and water are mixed to form slurry and then spray dried to form granules. The prepared particle size is controllable, no shaping is required, and cost is saved.

[0010] However, even though these studies have used different preparation methods to obtain negative electrode materials with stable electrochemical properties, and have modified them based on the volume effect of silicon to reduce the reconstruction and rupture of the SEI film; and have used the composite of carbon materials to increase the conductivity of the material to a certain extent, and have obtained excellent cycle stability. However, the current reported research still faces many severe challenges: First, in terms of preparation technology, only trace experiments can be carried out when using methods such as mechanical ball milling, chemical vapor deposition (CVD), and sol-gel method, and it is difficult to achieve large-scale industrial production; and when selecting graphite carbon materials, there are very few reports on inventions for further processing of graphite. Second, in terms of technical originality, most inventions have also studied the doping or coating of cracked carbon and metal oxides, but there are few reports on the use of the synergistic effect of cracked carbon and trace metal oxide TiO2, and the clever design of assemblies with graphite as the core and nano-silicon sheets, cracked carbon and TiO2 composites as the coating layer. Third, in terms of economic benefits, the research on these silicon-carbon materials is either complicated and costly, or the volume expansion of silicon materials is not fully resolved, resulting in a sharp decline in capacity and reduced electrochemical performance (e.g., the silicon-carbon composite material disclosed in CN112310363A of Huawei Technologies Co., Ltd. has a capacity retention rate of ~80% after 500 cycles; the silicon-carbon composite material disclosed in CN110021749A has an initial discharge capacity of 2144 mAh / g at a rate of 0.1C, and a capacity retention rate of 84% after 40 cycles). These have hindered the practical application of silicon-carbon negative electrode materials. Summary of the invention

[0011] In order to solve the above-mentioned problems existing in silicon-carbon negative electrode composite materials, the present invention provides a method for preparing titanium oxide-doped silicon-carbon lithium-ion battery negative electrode materials by sand grinding combined with spray drying. The method is a simple and scalable method for preparing silicon-carbon composite negative electrode materials, which can prepare silicon-carbon composite negative electrode materials with excellent electrochemical properties.

[0012] To achieve the above object, the technical solution adopted by the present invention is:

[0013] A method for preparing a titanium oxide-doped silicon-carbon lithium ion battery negative electrode material by sand grinding combined with spray drying comprises the following steps:

[0014] 1) Dispersing micron-sized Si particles recovered from solar photovoltaic cells, commercial graphite, and carbon source polyvinylpyrrolidone (PVP) in a solvent, and then pouring them into a sand mill for sand grinding to obtain a uniform and viscous mixed slurry;

[0015] 2) A certain amount of carbon source PVP and titanium oxide precursor are further added to the mixed slurry, and after being evenly mixed, the mixture is heated and stirred, and a certain amount of solvent is evaporated to obtain a viscous precursor slurry;

[0016] 3) The obtained precursor slurry is spray-dried, a large amount of powder is collected and further calcined and annealed to obtain a silicon-carbon composite negative electrode material.

[0017] In step 1), the average particle size of the micron-sized Si particles is 5-15 μm, and the particle size of the small nano-silicon fragments after sand grinding is 200-500 nm.

[0018] The solvent in step 1) is anhydrous ethanol or deionized water or a mixed solvent of the two, the speed of the sand mill is 800-1200 r / min, and the sand milling time is 6-20 hours.

[0019] In step 1), the graphite is artificial graphite or natural graphite, and the particle size is 10-20 μm.

[0020] The titanium oxide precursor in step 2) is tetrabutyl titanate, TiO2 or titanium tetrachloride.

[0021] The inlet temperature of the spray dryer in step 3) is 120-260° C., the outlet temperature is 50-80° C., and the protective gas is nitrogen.

[0022] During the calcination and annealing in step 3), the protective gas is an inert gas such as argon or argon-hydrogen mixed gas.

[0023] In step 3), the calcination annealing is performed at a rate of 3 to 5°C / min, and the temperature is 700-900°C.

[0024] The average particle size of the silicon-carbon negative electrode composite material prepared by the present invention is 8-20 μm.

[0025] In the silicon-carbon composite negative electrode material, silicon accounts for 15wt.%-30wt.%, graphite accounts for 55wt.%-80wt.%, PVP accounts for 20wt.%-30wt.%, and the doping amount of titanium oxide precursor accounts for 3wt.%-5wt.% of the total silicon.

[0026] The technical advantages of the present invention are as follows: First, in terms of preparation technology, large-scale production can be achieved by combining sand milling and spray drying processes. In particular, commercial graphite is further sand milled to increase the contact area between graphite and silicon without destroying the graphite structure. The electrostatic force and rich groups between silicon, graphite and PVP containing a polymer chain carbon source in the liquid phase form an excellent structurally stable self-assembly. Second, in terms of technical originality, a silicon-carbon composite material with graphite as the core and fragmented nano-silicon, carbon, and metal oxide as the coating layer is prepared by a simple method, giving full play to the synergistic effect of the carbon source and TiO2. The cracked carbon enhances the conductivity and structural stability of the composite material and effectively inhibits the volume expansion of silicon; the trace doping of TiO2 improves the silicon interface compatibility, stabilizes the formation of the SEI film, and greatly improves the electrochemical stability of the silicon-carbon composite material. Thirdly, in terms of economic benefits, the present invention utilizes waste silicon from solar photovoltaic cells recycled at a low price as raw material, and uses a simple, controllable, and low-energy preparation method, which greatly reduces the cost of silicon-carbon composite negative electrode materials, fully demonstrating the industrial use value of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the sample preparation process of Example 1 of the present invention.

[0028] Figure 2 1 is a scanning electron microscope photograph of the micron Si particles used in the present invention before and after sand grinding.

[0029] Figure 3 : are scanning electron microscope photographs of the commercial graphite used in the present invention before and after sand grinding.

[0030] Figure 4 These are scanning electron microscope photos and transmission electron microscope photos of the final sample prepared in Example 1 of the present invention.

[0031] Figure 5 This is the cycle curve of the sample prepared in Example 1 of the present invention at a current density of 800 mA / g.

[0032] Figure 6 This is the cycle curve of the sample prepared in Example 2 of the present invention at a current density of 800 mA / g.

[0033] Figure 7 This is the cycle curve of the sample prepared in Example 3 of the present invention at a current density of 800 mA / g. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0035] Example 1

[0036] A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying

[0037] First, weigh 220g of micron Si powder, disperse it in 2.5kg of anhydrous ethanol, mix it evenly and put it into a sand mill, stir it in a single tank for 30 minutes, the speed is 60r / min, and then sand mill it for 10h at a speed of 1000r / min. After sand milling, weigh 660g of commercial graphite and 300g of PVP (Mw=58000) respectively, disperse them in 7kg of anhydrous ethanol, mix them evenly and put them into a sand mill, stir them in a single tank for 30 minutes, the speed is 60r / min, sand mill them for 6h at a speed of 1100r / min. After completion, a uniformly dispersed silicon-graphite mixed slurry is obtained. Then, the obtained mixed slurry is taken out and put into a planetary mixer, and 300g of PVP and 30g of tetrabutyl titanate are added and stirred thoroughly, and the stirring frequency is set to 30Hz for 1h. After that, the excess ethanol is evaporated by heating and stirring to obtain a spray precursor solution, and its solid content is maintained at ~35wt.%. Secondly, the spray dryer inlet temperature was set to 160°C, the nitrogen N2 intake volume was 4L / min, the liquid pump speed was 50r / min, and the air pressure was 6Mpa. After spraying for about 3 hours, a large amount of silicon-carbon precursor powder was collected. Finally, the precursor powder was calcined and annealed, loaded into a crucible and placed in a high-temperature sintering furnace, heated to 900°C at 5°C / min, and annealed for 3 hours, during which argon Ar was introduced as a protective gas. After naturally cooling to room temperature, the final silicon-carbon negative electrode composite material was obtained. (Recorded as sample 1)

[0038] Figure 3 The scanning electron microscope image shows that the particles of sample 1 are evenly distributed and have an irregular spherical shape of approximately 10 to 20 μm.

[0039] 0.2 g of the final sample, 10% acetylene black and 10% sodium carboxymethyl cellulose (CMC) were dissolved in deionized water to form a uniform slurry, which was applied to the copper foil current collector and dried in vacuum at 80°C for 12 hours to prepare the electrode. A mixed solution of 5%:90% FEC (fluoroethylene carbonate) and 1.0 mol / L LiPF6 / EC / DEC / DMC was used as the electrolyte, in which LiPF6 was the conductive salt, EC (ethylene carbonate) / DEC (diethyl carbonate) / DMC (dimethyl carbonate) was the composite solvent, and the volume ratio of the three (EC:DEC:DMC) was 1:1:1. A CR2025 button cell was assembled with the above electrodes using a metal lithium sheet as the negative electrode and a microporous polypropylene membrane (Cellgard 2400) as the separator. The cells were charged and discharged at current densities of 0.3 A / g and 0.8 A / g, respectively. The voltage range of charge and discharge was 0.01-3.0 V. The battery test results are listed in Table 1.

[0040] Figure 4This is the test result of the silicon-carbon negative electrode material obtained in Example 1 at a current density of 0.8 A / g. It can be seen that the silicon-carbon negative electrode material still has a capacity of 876.6 mAh / g and a capacity retention rate of 88.3% after 500 cycles at 0.8 A / g.

[0041] Example 2

[0042] A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying

[0043] First, weigh 220g of micron Si powder, disperse it in 2.5kg of anhydrous ethanol, mix it evenly, and then put it into a sand mill. Stir it in a single tank for 30 minutes at a speed of 60r / min, then sand grind it for 10h at a speed of 1000r / min. After sand grinding, take it out for use. Then, weigh 6g of commercial graphite and add it to the ball mill, set the speed to 700r / min, and the time to 6h. According to the solid content of the sand-milled silicon slurry, take the slurry containing Si2.0g and mix it with the ball-milled graphite, and add 5.5g PVP carbon source and 16.67g titanium tetrachloride and stir evenly, and the solid content is controlled at ~35%. Secondly, set the spray dryer inlet temperature to 160℃, the nitrogen N2 intake volume to 4L / min, the liquid pump speed to 50r / min, and the air pressure to 6Mpa. After spraying for about 3h, a large amount of silicon-carbon precursor powder is collected. Finally, the precursor powder was calcined and annealed, placed in a crucible and placed in a high-temperature sintering furnace, heated to 900°C at 5°C / min, and annealed for 3 hours, with argon Ar introduced as a protective gas. After naturally cooling to room temperature, the final silicon-carbon negative electrode composite material was obtained. (Recorded as Sample 2)

[0044] The scanning electron microscope image shows that the particles of sample 2 are evenly distributed and have an irregular spherical shape of approximately 10 to 20 μm.

[0045] The counter electrode, electrolyte, battery assembly and testing method of the battery are the same as those in Example 1. The test results of the battery are listed in Table 1.

[0046] Example 3

[0047] A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying

[0048] First, weigh 220g of micron Si powder, disperse it in 2.5kg of anhydrous ethanol, mix it evenly, and then put it into a sand mill. Stir it in a single tank for 30 minutes at a speed of 60r / min, then sand mill it for 10h at a speed of 1000r / min. Then, weigh 660g of commercial graphite and 600g of PVP, disperse them in 7kg of anhydrous ethanol, mix them evenly and put them into a planetary mixer, continue to add 30g of tetrabutyl titanate and stir them thoroughly, set the stirring frequency to 30Hz, and the time to 1h. After that, heat and stir to evaporate the excess ethanol to obtain a spray precursor solution, the solid content of which is maintained at ~35wt.%. Secondly, set the spray dryer inlet temperature to 160°C, the nitrogen N2 intake volume to 4L / min, the liquid pump speed to 50r / min, the air pressure to 6Mpa, and collect a large amount of silicon-carbon precursor powder after spraying for about 3h. Finally, the precursor powder was calcined and annealed, placed in a crucible and placed in a high-temperature sintering furnace, heated to 900°C at 5°C / min, and annealed for 3 hours, with argon Ar introduced as a protective gas. After naturally cooling to room temperature, the final silicon-carbon negative electrode composite material was obtained. (Recorded as Sample 3)

[0049] The scanning electron microscope image shows that the particles of sample 3 are evenly distributed and have an irregular spherical shape of approximately 10 to 20 μm.

[0050] The counter electrode, electrolyte, battery assembly and testing method of the battery are the same as those in Example 1. The test results of the battery are listed in Table 1.

[0051] Example 4

[0052] A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying

[0053] First, weigh 220g of micron Si powder, disperse it in 2.5kg of anhydrous ethanol, mix it evenly, and put it into a sand mill. Stir it in a single tank for 30 minutes at a speed of 60r / min, and then sand grind it for 10h at a speed of 1000r / min. After sand grinding, weigh 660g of commercial graphite and 300g of PVP (Mw=58000) respectively, disperse them in 7kg of anhydrous ethanol, mix them evenly and put them into a sand mill. Stir it in a single tank for 30 minutes at a speed of 60r / min, sand grind it for 6h at a speed of 1100r / min. After completion, a uniformly dispersed silicon graphite slurry is obtained. Then, take out the obtained mixed slurry and put it into a planetary mixer. Continue to add 300g of PVP and stir it thoroughly. Set the stirring frequency to 30Hz and the time to 1h. After that, heat and stir to evaporate the excess ethanol to obtain a spray precursor solution, the solid content of which is maintained at ~35wt.%. Secondly, the spray dryer inlet temperature was set to 160°C, the nitrogen N2 intake volume was 4L / min, the liquid pump speed was 50r / min, and the air pressure was 6Mpa. After spraying for about 3 hours, a large amount of silicon-carbon precursor powder was collected. Finally, the precursor powder was calcined and annealed, loaded into a crucible and placed in a high-temperature sintering furnace, heated to 800°C at 5°C / min, and annealed for 3 hours, during which argon Ar was introduced as a protective gas. After naturally cooling to room temperature, the final silicon-carbon negative electrode composite material was obtained. (Recorded as sample 4)

[0054] The scanning electron microscope image shows that the particles of sample 4 are evenly distributed and have an irregular spherical shape of approximately 10 to 20 μm.

[0055] The counter electrode, electrolyte, battery assembly and testing method of the battery are the same as those in Example 1. The test results of the battery are listed in Table 1.

[0056] Example 5

[0057] A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying

[0058] First, weigh 220g of micron Si powder, disperse it in 2.5kg of anhydrous ethanol, mix it evenly, and put it into a sand mill. Stir it in a single tank for 30 minutes at a speed of 60r / min, then sand it for 10h at a speed of 1000r / min. After sand milling, weigh 660g of commercial graphite and disperse it in 7kg of anhydrous ethanol, mix it evenly and put it into a sand mill. Stir it in a single tank for 30 minutes at a speed of 60r / min, sand it for 6h at a speed of 1100r / min. After completion, a uniformly dispersed silicon graphite slurry is obtained. After that, heat and stir to evaporate the excess ethanol to obtain a spray precursor solution, the solid content of which is maintained at ~35wt.%. Secondly, set the spray dryer inlet temperature to 160°C, the nitrogen N2 intake volume to 4L / min, the liquid inlet pump speed to 50r / min, the air pressure to 6Mpa, and collect a large amount of silicon-carbon precursor powder after spraying for about 3h. Finally, the precursor powder was calcined and annealed, placed in a crucible and placed in a high-temperature sintering furnace, heated to 700°C at 5°C / min, and annealed for 3 hours, with argon Ar introduced as a protective gas. After naturally cooling to room temperature, the final silicon-carbon negative electrode composite material was obtained. (Recorded as Sample 5)

[0059] The scanning electron microscope image shows that the particles of sample 5 are evenly distributed and have an irregular spherical shape of approximately 10 to 20 μm.

[0060] The counter electrode, electrolyte, battery assembly and testing method of the battery are the same as those in Example 1. The test results of the battery are listed in Table 1.

[0061] Table 1 Summary of test results of Examples 1 to 5

[0062]

[0063] According to the comparison of the results in Table 1, the negative electrode material of Example 1 exhibits the best comprehensive battery performance. After 500 cycles at a current density of 0.8A / g, it still has a discharge capacity of 876.6mAh / g, and the capacity retention rate is as high as 88.3%. In terms of the advantages of the sand milling combined with spray drying preparation process, the excellent performance of Example 1 fully illustrates the advantages of this process path: first, the sand milling of graphite can reduce the particle size of graphite, increase the specific surface area of ​​graphite, and thus increase the interface bonding area with other components in the composite material; second, the introduction of carbon can enhance the conductive contact between graphite and silicon, thereby enhancing battery performance; third, the introduction of metal oxide TiO2 can effectively enhance the interface compatibility and electrochemical performance of the negative electrode material.

[0064] Compared with Example 1, the graphite treatment method of Example 2 adopts ball milling treatment, which has the following defects: First, the ball milling process fails to effectively achieve kilogram-level macro-processing of graphite materials; second, the particle size of the graphite after ball milling fails to be effectively reduced, and the coverage area with silicon particles fails to be increased, and the ball milling treatment causes the graphite to introduce additional dangling groups, which is not conducive to the interface compatibility of the material. Therefore, after 500 cycles in Example 2, only a low discharge specific capacity and capacity retention rate are maintained.

[0065] Compared with Example 1 and Example 2, the graphite of Example 3 was directly mixed with other raw materials without treatment, and the comprehensive battery performance of the battery was significantly inferior to that of Example 1 and Example 2. From the above comparison, it can be seen that the graphite and silicon are composited without being crushed by the high-speed shear force of the sand mill or ball mill, resulting in a reduction in the contact area between the graphite and silicon, and failing to output good electrochemical performance.

[0066] Compared with Example 1, Example 4 is not doped with trace amounts of titanium oxide. Although the initial discharge capacity reaches 1694.5 mAh / g, the capacity decays rapidly after 500 cycles, and the retention rate is only 50.8%. The above comparison results highlight that the introduction of metal oxide TiO2 can effectively enhance the interface compatibility and electrochemical performance of the negative electrode material.

[0067] Compared with Example 1, Example 5 was not doped with trace amounts of titanium oxide and PVP, and only maintained a minimum discharge capacity of 503.6 mAh / g after 500 cycles, with the worst overall performance. The above comparison shows that the sample prepared by spraying only silicon and graphite after sand grinding in Example 5 is only a physical mixture of the two raw materials, indicating that the absence of PVP makes it impossible for silicon and graphite particles to form conductive bonding and improve interface compatibility.

[0068] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying, characterized in that: The following steps are involved: 1) Dispersing micron-sized Si particles, graphite and PVP recovered from solar photovoltaic cells in a solvent, and then pouring them into a sand mill for sand grinding to obtain a mixed slurry; The average particle size of the micron-sized Si particles is 5-15 μm, and the particle size of the small fragments of nano-silicon obtained after sand grinding is 200-500 nm; The solvent is anhydrous ethanol or deionized water or a mixed solvent of the two, the sand mill speed is 800-1200 r / min, and the sand milling time is 6-20 h; 2) Add PVP and titanium oxide precursor to the mixed slurry, mix well, heat and stir, and evaporate and remove the solvent to obtain a precursor slurry; The titanium oxide precursor is tetrabutyl titanate, TiO2 or titanium tetrachloride; 3) The obtained precursor slurry is spray dried, the inlet temperature of the spray dryer is 120-260°C, and the outlet temperature is 50-80°C. A large amount of powder is collected and calcined and annealed at 700-900°C to obtain a silicon-carbon composite negative electrode material.

2. The method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand milling combined with spray drying according to claim 1, characterized in that: The graphite in step 1) is artificial graphite or natural graphite, and the particle size is 10-20 μm.

3. The method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by sand grinding combined with spray drying according to claim 1, characterized in that: The protective gas during calcination and annealing in step 3) is an inert gas.

4. The silicon-carbon composite negative electrode material obtained according to the preparation method according to any one of claims 1 to 3.

5. The silicon-carbon composite negative electrode material according to claim 4, characterized in that: In the silicon-carbon composite negative electrode material, silicon accounts for 15 wt.%-30 wt.%, graphite accounts for 55 wt.%-80 wt.%, PVP accounts for 20 wt.%-30 wt.%, and the doping amount of titanium oxide precursor accounts for 3 wt.%-5 wt.% of the total silicon.

Citation Information

Patent Citations

  • Preparation method of silicon carbon lithium ion battery cathode material

    CN102790204A

  • A silicon-carbon composite material for lithium-ion batteries and its preparation method

    CN109216686B

  • Silicon carbon negative electrode material, preparation method thereof and battery

    CN110021749A

  • Silicon-carbon composite material, preparation method thereof and lithium ion battery

    CN112310363A

  • Method for preparing lithium ion battery graphite negative electrode material by spray drying method

    CN113258063A